Ratification of directors' breaches of duty : problems, perspectives and scope for reform / S. T. Lingam - T. Lingam, S. (Faculty of Administratron and Law, 2001)
The ability of the company to avoid transactions made by directors in breach of their duties as well as its ability to make the wrongdoing directors personally liable to it for such breach may be hindered where there has been a "ratification" of such breach. This article seeks to highlight the problems associated with the present legal position regarding ratification of a director's breach of duty and to suggest possible reforms taking into account developments in other common law jurisdictions.